Decision Model of Use E-Money in Covid-19 Pandemic Situation - Krismawintari, Ni Putu Dyah; Komalasari, Yeyen; Utama, I Gusti Bagus Rai; Trimurti, Christimulia Purnama; Junaedi, I Wayan Ruspendi (Technium Social Sciences Journal, 2020)
this research was conducted to determine what variables influenced the e-money usage decision model during the Covid-19 pandemic. The survey involved 160 respondents during the Covid-19 pandemic. This research uses a quantitative approach using structural analysis of the SEM-AMOS model. A person’s decision to use e-money is significantly influenced by concerns about Covid-19 transmission when they leave the house. Other variables are the frequency of someone searching for news about Covid-19, transaction behavior, ease of electronic money, efforts to attract the use of E-Money by service providers, and the use of cash when COVID-19 does not have a significant effect. Suggestions that can be given if e-money services want to increase public interest in using non-cash services, it is necessary to increase the security of transactions and provide facilities or service features that can be accessed from home.